South African strides towards attaining green analytical methods and a green environment for environmental analysis of pharmaceuticals - Lawrence Mzukisi Madikizela; Vusumzi Emmanuel Pakade (Green Analytical Chemistry)
The occurrence of pharmaceuticals in South African water systems was established in the early 2000′s. However, the metabolites of these chemicals were only established in South African waters after two decades of pharmaceutical analysis in water. The analytical methods focussed largely on traditional approaches that include solid-phase extraction and chromatographic analysis. Thus far, there is limited work that was designed to fulfill the green chemistry initiatives while performing the analysis of pharmaceuticals in South African waters. Such work is comprehensively reviewed in this paper with an attempt to highlight the research gaps for future exploration. In South Africa, the green analytical chemistry procedures utilized for pharmaceutical analysis include miniaturized sample preparation methods, the application of reusable solid-phase adsorbents, and novel materials for passive sampling. In recent years, multi-residue drug analysis has been a focal point rather than a single pharmaceutical analysis. Computational tools including multivariate optimization and studying the monomer-template interactions in molecular imprinting of solid-phase extraction sorbents have been investigated. Similarly to the developed countries, intensive research on greening analytical methods in South Africa is still required.